2016
DOI: 10.4103/0975-5950.196137
|View full text |Cite
|
Sign up to set email alerts
|

The newer aspect of dexmedetomidine use in dentistry: As an additive to local anesthesia, initial experience, and review of literature

Abstract: Introduction:Despite the availability of a wide variety of pharmacological agents in the field of anesthesia, there has always been a continuous search for newer local anesthetic agents with improved efficacy, potency, and better handling properties. Dexmedetomidine, a selective alpha-2 adrenergic receptor agonist, is an emerging agent for provision of additive local anesthetic effect if used with conventional local anesthetics, which can be implicated in dentistry for performing many minor oral surgical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The results of the present study demonstrated that the addition of DEX to LB significantly shortened the latency. This is in congruence with other studies that reported similar observations of rapid onset of anesthesia [ 9 10 11 13 15 ]. This could be due to the synergistic action of the individual drugs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study demonstrated that the addition of DEX to LB significantly shortened the latency. This is in congruence with other studies that reported similar observations of rapid onset of anesthesia [ 9 10 11 13 15 ]. This could be due to the synergistic action of the individual drugs.…”
Section: Discussionsupporting
confidence: 93%
“…The overall difference in both groups during the procedure was statistically significant (P < 0.05). Similar observations were made by others, who noticed an increase in pain threshold values when combining DEX with lignocaine [ 11 16 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results showed that onset and duration of anesthesia were faster and prolonged in the peripheral group as compared to other groups with insignificant hemodynamic changes amongst the groups. This study concluded that the addition of 7 mg/L dexmedetomidine to lidocaine perineurally boosts the onset of action and prolongs the duration of anesthesia [ 6 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 6 In particular, DEX has been shown to enhance the potency of a local anesthetic (eg, lidocaine) without significant systemic effects following local injection into oral mucosa. 7 The exact mechanism by which DEX prolongs local anesthetic duration has not been fully clarified. However, DEX has a direct blockade effect on tetrodotoxin-resistant sodium (Na + ) channels.…”
mentioning
confidence: 99%